Una vida más allá de las fronteras: Benedict Anderson (1936-2015) - Bayona, Jorge (2017)
This is a brief overview of Benedict Anderson’s life and work. As one of the world’s preeminent Southeast Asianists his contributions to the study of Indonesia, Thailand, and the Philippines continue to influence newer generations of scholars. Knowledge of some of the key factors of his life and intellectual work ?such as his multicultural upbringing, mastery of multiple languages, and vigorous engagement with the major political events of his lifetime? we may understand how a book such as Imagined Communities came about.